Studi Awal Historiografi Islam Abad Pertengahan - Deden Zaenal Muttaqin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2009)
This article is a study focused on the rise of islamic historiography in the middle age. At that time many Muslim historians developed new methodology and trend on their study. They wrote their study based on rational interpretation and not merely focused on political aspect, but expanded to other aspects such as geographical and natural The fact of these rising study had strongly influenced by renaisans of Islam.